Chain walking of allylrhodium species towards esters during rhodium-catalyzed nucleophilic allylations of imines - Martínez, Jose I.; Smith, Joshua S.; Hepburn, Hamish B.; Lam, Hon Wai (Wiley-VCH Verlag, 2015)
Allylrhodium species derived from δ-trifluoroboryl β,γ-unsaturated esters undergo chain walking towards the ester moiety.The resulting allylrhodium species react with imines to give products containing two new stereocenters and a Z-alkene. By using a chiral diene ligand, products can be obtained with high enantioselectivities, where a pronounced matched/mismatched effect with the chirality of the allyltrifluoroborate is evident.